Eye Structure and Chemical Details of the Retinal Layer of Juvenile Queen Danio Devario regina (Fowler, 1934) - Boonyoung, Piyakorn; Senarat, Sinlapachai; Kettratad, Jes; Poolprasert, Pisit; Yenchum, Watiporn; Jiraungkoorskul, Wannee (Agriculture and Natural Resources, 2015)
The eye structures and chemical details of the retinal layer in juvenile Queen Danio—Devario regina, an ornamental fish—were histologically investigated under a light microscope. Sample fish were collected from the Tapee River, Nakhon Si Thammarat province, Thailand and their heads were exclusively prepared using a standard histological technique. The results revealed that the eye of D. regina was composed of three layers—inner, middle and external—based on histological organization and cell types. The inner layer was composed of 10 layers; 1) pigment epithelium, 2) photoreceptor layer, 3) outer liming membrane, 4) outer nuclear layer, 5) outer plexiform layer, 6) inner nuclear layer, 7) inner plexiform layer, 8) ganglion cell layer, 9) optic nerve layer and 10) inner limiting membrane, respectively. The localization and chemical details showed that a periodic acid-Schiff reaction for the detection of glycoprotein was intensive in the pigment epithelial layer whereas the inner plexifrom layer had only a slight reaction. Reaction of aniline blue was employed for the detection of mucopolysaccharide which was slightly positive for three layers—the outer limiting membrane, outer plexiform and inner plexiform.